Perceived stress in dental students of a private university in Acapulco, Mexico - Guadarrama-Analco, Jacqueline (2023)
Stress is a common aspect of daily life, but its negative impact emerges when it disrupts normal daily functioning. It triggers physiological changes within the body's systems, influencing behavior and emotions. Objective: This study aims to assess the frequency of perceived stress among dental students attending a private institute in Acapulco, Guerrero, Mexico. Material and methods: A descriptive cross-sectional study was conducted in November 2020. The survey targeted seventy-one Dentistry students ranging from the first to seventh semester. The survey collected sociodemographic information and utilized the ten-item Perceived Stress Scale, developed by Cohen, which employs a Likert-type scale with five categorical values. The scores were analyzed using the R statistical program. Simple frequencies of variables were obtained, and Student's t-test was employed to compare students' stress levels. The odds ratio (OR), along with its 95 % confidence interval (CI 95%) using the Miettinen method, was calculated to quantify stress risk based on gender and semester. Results: Among the participants, 60 % (43/71) experienced high levels of stress. Specifically, women accounted for a higher occurrence of stress at 70 % (30/43). The association of high stress was particularly prominent among students in the last semester (OR = 2.88; 95 % CI = 1.07-7.71). Conclusion: The findings suggest that a significant portion, at least six out of ten students, experience elevated stress levels. The study underscores the importance of dental educators identifying and addressing stressful situations among students, thereby facilitating the referral of cases in need of psychological support.